KEPASTIAN HUKUM PERIZINAN BERUSAHA UMKM SEBAGAI UPAYA PEMBERDAYAAN DAN PENGEMBANGAN UMKM DI KOTA MEDAN - Chrismo H Sitorus; Mahmul Siregar; Joiverdia Arifiyanto (Smart Education, 2025)
Abstract:MSMEsstillfacevariousobstacles, especially in termsofregulationsandlicensingwhich are oftenconfusingand not in syncbetweenlawsandtheirimplementingregulations. Changestotheprovisions in Law Number 6 of 2023 concerningJobCreation, such as articlesthat are open tomultipleinterpretations, make MSME actorsreluctanttotakecareofpermitsdueto legal uncertainty, complicatedprocesses, andconcernsabouttaxes. Therefore, itisnecessarytostrengthenthe legal umbrella, simplifythebureaucracy, andoptimizeempowermentfromthegovernmentsothatMSMEscandevelop, competehealthily, andbecomethe main pillars in supportingthenationaleconomy. Thesematerials were thenanalyzedqualitativelywith a descriptiveanalyticalapproach. Legal certainty in theempowermentanddevelopmentofMSMEsthroughbusinesslicensingbasedon Law Number 6 of 2023 concerningJobCreationand Law Number 20 of 2008 concerningMicro, Smalland Medium Enterprises isseenfromArticle 87 whichstatesthewordsexemptlicensingfeeswhileArticle 92 Paragraph 2, thisprovidesdifferentinterpretationsofwhethermicrobusinessesactuallygetfreefeesor not. Becausethephrase